Exploring Banyumas Local Wisdom as a Contextual Basis for Character Education: Insights from Elementary School Teachers in Indonesia - Fadilla Aisah Nurikhsani; Wasino Wasino; Eko Handoyo (Proceedings of International Conference on Science, Education, and Technology, 2026)
Local wisdom carries historically and culturally tested values, yet its potential as a foundation for character education in elementary schools often remains unrealized in practice. Banyumas local wisdom, with its distinctive and egalitarian character, represents an underexplored cultural resource in the context of character education. Within the Merdeka Curriculum, which explicitly accommodates local wisdom integration, empirical studies on how Banyumas local wisdom can serve as a contextual basis for character education in elementary schools remain scarce. This study aims to explore Banyumas local wisdom as a contextual basis for character education in elementary schools. Using a descriptive qualitative approach through semi-structured interviews with 15 grade IV–VI teachers in Banyumas Regency, data were analyzed using Braun and Clarke's (2006) thematic analysis. The findings reveal that Banyumas local wisdom carries authentic values closely connected to students' everyday lives. The values of cablaka, collective participation, and egalitarianism prove relevant to elementary students' character formation. Although the Merdeka Curriculum has provided space for integration, local wisdom remains suboptimally utilized due to the absence of structured guidelines. These findings demonstrate that Banyumas local wisdom holds a strong value foundation for character education and urgently warrants development as a structured basis for character learning.